2020
DOI: 10.3389/fmicb.2020.01482
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Serotype, Antibiotic Susceptibility, and Genotype of Salmonella in Eggs From Poultry Farms and Marketplaces in Yangling, Shaanxi Province, China

Abstract: Poultry products such as eggs provide essential nutrients to the human body and thus play vital roles in the human food network. Salmonella is one of the most notorious foodborne pathogens and has been found to be prevalent in eggs. To better understand the characteristics of Salmonella in eggs, we investigated the prevalence of Salmonella spp. in 814 fresh eggs collected from poultry farms and retail marketplaces in Yangling, Shaanxi Provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
3
19
1
1
Order By: Relevance
“…These isolates were subjected to antimicrobial susceptibility assay and further genomic characterization. The positive rate found in this study was lower than that observed in eggs collected from poultry farms in Yangling, Shaanxi province (6.6%) (Li et al, 2020a ), and Shandong province (Zhao et al, 2021 ) and higher than that obtained by Li et al (0.5%) across China in 2016 (Li et al, 2020b ).…”
Section: Discussioncontrasting
confidence: 74%
“…These isolates were subjected to antimicrobial susceptibility assay and further genomic characterization. The positive rate found in this study was lower than that observed in eggs collected from poultry farms in Yangling, Shaanxi province (6.6%) (Li et al, 2020a ), and Shandong province (Zhao et al, 2021 ) and higher than that obtained by Li et al (0.5%) across China in 2016 (Li et al, 2020b ).…”
Section: Discussioncontrasting
confidence: 74%
“…Serotyping is an effective approach to evaluating modes of transmission to develop strategies for preventing disease spread within poultry facilities (30). We found that S. Thompson, which is a member of Salmonella serogroup C1 commonly associated with disease in humans (31) and isolated in poultry and poultry eggs (8,28,32), was the most prevalent isolate in the present study. This is in contrast to studies in Shanghai and Sichuan that had identified S. Enteritidis as the most common serovar in commercial chicken farms (25,33), while S. Indiana was found to be dominant in Shandong (34), and S. Weltevreden was dominant in Central Vietnam (35).…”
Section: Discussionsupporting
confidence: 48%
“…We found that S . Thompson, which is a member of Salmonella serogroup C1 commonly associated with disease in humans ( 31 ) and isolated in poultry and poultry eggs ( 8 , 28 , 32 ), was the most prevalent isolate in the present study. This is in contrast to studies in Shanghai and Sichuan that had identified S .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Among the 14 antibiotics used in this study, the resistance rates of all Salmonella isolates to 11 antibiotics in conventional chicken were higher than those from chickens fed on antibiotic-free diets. The average MDR rate (20.2%, 22/109) of Salmonella isolates from chickens fed on antibiotic-free diets was significantly lower than the rates of 100% among 63 isolates examined by Yang et al (19) from conventional farms in a similar geographical region, and also lower than that from other poultry farms in China (43). These data indicated that the use of antibiotics may promote the development of MDR Salmonella (44).…”
Section: Discussionmentioning
confidence: 94%